2023
DOI: 10.1681/asn.0000000000000154
|View full text |Cite
|
Sign up to set email alerts
|

miR-147 Represses NDUFA4, Inducing Mitochondrial Dysfunction and Tubular Damage in Cold Storage Kidney Transplantation

Abstract: Background Kidney injury due to cold storage–associated transplantation (CST) is a major factor determining the outcome of renal transplant, for which the role and regulation of microRNAs remain largely unclear. Methods The kidneys of proximal tubule Dicer (an enzyme for microRNA biogenesis) knockout mice and their wild-type littermates were subjected to CST to determine the function of microRNAs. Small RNA sequencing then profiled microRNA expression i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…We employed ATP depletion recovery model (ATP-DR) to induce renal tubular cell injury, mimicking the in vivo IRI condition[ 10 , 31 ] . PI and Hoechst staining demonstrated that P110 alleviated cell death induced by ATP-DR (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We employed ATP depletion recovery model (ATP-DR) to induce renal tubular cell injury, mimicking the in vivo IRI condition[ 10 , 31 ] . PI and Hoechst staining demonstrated that P110 alleviated cell death induced by ATP-DR (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This gene demonstrates significant tissue-specific expression in the liver and brain ( 48 ). NDUFA4 is a target of miR-147, and the inhibition of miR-147, coupled with the overexpression of NDUFA4, can induce mitochondrial damage and renal tubular cell death ( 49 ). A deficiency in NDUFA4 expression can exacerbate oxidative stress, further predisposing to the onset of diabetes ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is tempting to speculate about the role of miR-147b in renal inflammation. Interestingly, a recent publication described renal injury due to the induction of miR-147 during cold-storage-associated transplantation [ 39 ]. miR-147 suppressed NDUFA4, resulting in mitochondrial damage and renal tubule cell death.…”
Section: Discussionmentioning
confidence: 99%